Estimativa de variacao anual da reflexao da vegetacao atraves de imagens Landsat - Garcia, G. J.; Biazon, M. M. (My University, 1981)
Landsat images obtained in different periods were analysed with the aid of a transmission densitometer. Forest, pasture and crops were studied during Jan., April, July and Oct. and the results suggest the possibility of studying crop cycles using this method. -from Field Crop Abstracts
Estimation of annual variation of vegetation reflection through Landsat images